Implementation of the National Education Policy 2020 in Higher Education Institutions of Haryana: Curriculum Structure, Scheme Framework and Implementation Challenges (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The National Education Policy 2020 (NEP-2020) represents a transformative reform in the Indian higher education system aimed at promoting multidisciplinary learning, academic flexibility, skill development, and research orientation. One of the most significant reforms introduced under the policy is the Curriculum and Credit Framework for Undergraduate Programmes (CCFUGP), which allows students to pursue a four-year undergraduate programme with multiple entry and exit options. The framework integrates various course categories such as Discipline Specific Courses (DSC), Minor Courses (MIC), Multidisciplinary Courses (MDC), Skill Enhancement Courses (SEC), and Value Added Courses (VAC) to promote holistic education and interdisciplinary learning. Universities and colleges in Haryana have started implementing NEP reforms through different scheme-based academic structures including Scheme A, Scheme B, and Scheme C. These schemes provide flexibility for students to pursue multidisciplinary learning, major–minor combinations, and single-major specialization. The present study reviews the implementation of NEP-2020 in higher education institutions of Haryana with particular emphasis on curriculum structure, course categories, and scheme frameworks. The study also examines challenges faced during implementation, including curriculum variations across universities, rigid credit structures, infrastructure limitations, and lack of student awareness regarding course selection. The paper concludes by suggesting policy measures such as curriculum standardization, greater flexibility in credit allocation, faculty training programmes, and effective academic counselling systems to ensure successful implementation of NEP-2020 reforms in the state.